What is racism? - Katie Daynes (India Usborne, 2021)
A thoughtful anti-racism book for young children and their families. Answering young children's questions about racism is hard. This book gives both children and adults the language and sensitivity they need to talk about the topic. It gently explains what racism is, how it happens, why it is never acceptable and what each and every one of us can do to eradicate it. Written with expert advice and support from Show Racism the Red Card and child psychologist Dr Aayesha Mulla, this book uses the ever-popular question and answer flap format to explore this topic carefully and thoroughly.
Keywords: Sharing The Planet -- Sharing The Planet; Conflict -- Conflict